Association of the personal factors of culture, attitude and motivation with health behavior among adolescents in Malaysia - Hamzah, Siti Raba'ah; Suandi, Turiman; Ismail, Maimunah; Muda, Zulaiha (Informa UK, 2019)
This study was undertaken to determine the association of the personal factors of culture, attitude and motivation on health behavior among Malaysian adolescents. A cluster sampling technique was used and a total of 1,029 students with ages ranging from 15 to 17 years (M age = 15.9, SD = .637) were selected as respondents. The research instrument was a self-administered questionnaire covering health behavior, culture, attitude, and motivation towards health. The strongest linear relationship was found between culture and health behavior (r = .618, p = .001). Besides the culture of adolescents being the main predictor of health behavior (β = .365, p = .000), attitude (β = .283, p = .000) and motivation (β = .064, p = .033) also had significant independent effects on health behavior. Hence, culture, attitude and motivation should be taken into consideration in the promotion of health education, especially at school level.